Contrasting Effects of Environmental Concentrations of Sulfonamides on Microbial Heterotrophic Activities in Freshwater Sediments - Pesce, Stéphane; Kergoat, Laura; Paris, Laurianne; Billet, Loren; Besse-Hoggan, Pascale; Bonnineau, Chloé (Frontiers in Microbiology, 2021)
The sulfonamide antibiotics sulfamethoxazole (SMX) and sulfamethazine (SMZ) are regularly detected in surface sediments of contaminated hydrosystems, with maximum concentrations that can reach tens of µg kg-1 in stream and river sediments. Little is known about the resulting effects on the exposed benthic organisms. Here we investigated the functional response of stream sediment microbial communities exposed for 4 weeks to two levels of environmentally relevant concentrations of SMX and SMZ, tested individually. To this end, we developed a laboratory channel experiment where natural stream sediments were immersed in water contaminated with nominal environmental concentrations of 500 ng L-1 and 5000 ng L-1 of SMX or SMZ, causing their accumulation in surface sediments. The mean maximum concentrations measured in the sediment (about 2.1 µg SMX kg-1 dw and 4.5 µg SMZ kg-1 dw) were consistent with those reported in contaminated rivers. The resulting chronic exposure had various effects on the functional potential of the sediment microbial communities, according to the substance (SMX or SMZ), the type of treatment (high or low) and the measured activity, with a strong influence of temporal dynamics. Whereas the SMZ treatments resulted in only transient effects on the five microbial activities investigated, we observed a significant stimulation of the β-glucosidase activity over the 28 days in the communities exposed to the highest concentrations of SMX. Together with the stimulation of aerobic respiration at low SMX concentrations and the reduced concentration observed in the last days, our results suggest a potential biodegradation of sulfonamides by microbial communities from sediments. Given the key functional role of surface sediment microbial communities in streams and rivers, our findings suggest that the frequently reported contamination of sediments by sulfonamides is likely to affect biogeochemical cycles, with possible impact on ecosystem functioning.